Analisis Bahasa Jurnalistik Pada Headline Koran Hybird SumateraEkspres.ID - Megatria Agustin Sumiarti; Sumaina Duku; Jawasi Jawasi (ScidacPlus, 2023)
ABSTRACT: The development of print media from time to time always experiences developments, one of which is hybrid newspapers. Hybrid newspapers are digital-based printed newspapers that can be accessed at any time. This indicates that print media needs innovation to keep up with the times. In news writing, each journalist has different characteristics in writing news. The aim of this research is to determine the use of journalistic language in the headlines of the hybrid Sumatraekspres.id newspaper used. Researchers used descriptive qualitative methods. This type of descriptive qualitative method is used as an illustration of how journalistic language is used in the hybrid newspaper Sumatraekspres.id. The data collection techniques used in this research are observation, interviews and documentation. Apart from providing information, hybrid newspapers can also provide knowledge and insight for readers at large, in newspapers we find many different languages, as a communication tool that can help readers. understand communicatively, especially in writing journalistic language in newspapers. Writing journalistic language determines the information conveyed. Wrong writing can cause errors in meaning for those reading it. Therefore, careful analysis of journalistic language in the hybrid newspaper Sumatraekspres.id is needed before it is published and disseminated to the public and adjusts the characteristics of journalistic language according to Haris Sumadiria's theory. Journalistic language is the language used by a journalist to explain an event in a journalistic work. Every journalist has their own language in writing. However, we need to be careful about the accuracy of the data and the truth of what is happening in the field. From the research results, it can be concluded that the hybrid newspaper Sumatraekspres.id is quite good, but still violates the characteristics of short and concise, populist, logical and clear journalistic language..